Cytomegalovirus Hepatitis During Pregnancy. Issue 4 (1995) - Chan, Ying; Kean-Chong, Maria; Gonzalez, David; Apuzzio, Joseph
Abstract : Background: Although cytomegalovirus (CMV) is an uncommon cause of viral hepatitis during pregnancy, a definitive diagnosis is important because of the potential for congenital CMV. In the case reported here, a diagnosis of hepatitis caused by CMV was made after the more common viral pathogens had been ruled out. Case: A 17-year-old, 12-week pregnant patient was evaluated for fever and right upper quadrant tenderness. A serologic evaluation revealed elevated liver function levels and a positive maternal serology for CMV IgM. A diagnosis of hepatitis caused by CMV was made after the more common viral pathogens and drug-induced hepatitis had been ruled out. She was counseled about the potential effects of CMV on her fetus. Conclusion: A step-wise approach to the diagnosis of viral hepatitis during pregnancy is needed to determine the etiology because a potential teratogenic virus may be involved.